Pengaruh Citra Merek, Kualitas Layanan Dan Kenyamanan Tempat Terhadap Kepuasan Konsumen Pada Mie Gacoan Lowokwaru - Hanis Putri Kurnia Wati; Rois Arifin; Satria Putra Utama (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The type of data used in this study is quantitative data, quantitative data is the value described in numbers (numeric) using statistical methods. The technique used in this study was purposive sampling with 98 respondents on consumer satisfaction of Mie Gacoan Lowokwaru. The data analysis used is multiple linear regression analysis, t-test and F-test.The results showed that brand image partially had a positive and significant effect on consumer satisfaction at Lowokwaru Gacoan Noodles. Service quality partially has a positive and significant effect on consumer satisfaction at Lowokwaru Gacoan Noodles. Location partially has a positive and significant effect on customer satisfaction in Mie Gacoan Lowokwaru. Brand image, service quality and place convenience as locations simultaneously have a positive and significant effect on consumer satisfaction at Mie Gacoan Lowokwaru.  Keywords: Brand Image, Service Quality, Place Convenience, and Consumer Satisfaction.